PvdA congres 5-11-1977 Congresgebouw Den Haag. V.l.n.r. Liesbeth en Joop den Uyl. Achter Liesbeth: Peper - Morelis, Nick, (1977)
PvdA congres 5-11-1977 Congresgebouw Den Haag. V.l.n.r. Liesbeth en Joop den Uyl. Achter Liesbeth: Peper.